The psychological portrait as a tool to improve the subjective well-being of the client in the context of personal sales; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Kiseleva E. S. Elena Stanislavovna; Eremin V. V. Vasiliy Vasilievich; Yakimenko E. V. Elena Vladimirovna; Krakoveckaya I. V. Inna; Berkalov S. V. Sergey (2016, 2016)
Title screen